Comparison of visual meanings on the cover of Agatha Christie's Crooked House novel in 1986, 2000, 2009, and 2017 - Ayu Zulkadinityas; Iwan Gunawan; Ardianti Permata Ayu (Asosiasi Program Studi Desain Komunikasi Visual Indonesia (Asprodi DKV), 2025)
Changes in book cover design are a common practice among publishers, particularly for best-selling novels. This phenomenon is evident in Crooked House by Agatha Christie, which has undergone four distinct cover redesigns in 1986, 2000, 2009, and 2017. These design variations form the foundation of this study. The research aims to analyze the use of visual signs on the covers of Crooked House to identify, interpret, and compare the meanings conveyed through each visual element across different editions. A qualitative research method was employed, utilizing Charles Sanders Peirce’s semiotic theory, which consists of three core components: representamen (sign), object, and interpretant. The study also examines stylistic variations and design trends in each cover edition to explore how visual differences influence the transmission of meaning and the representation of the novel’s narrative essence. The findings indicate that, despite their visual diversity, each cover conveys a consistent underlying meaning and impression related to the novel’s thematic content. The variations among editions are influenced by contextual factors such as prevailing design trends of each era and the distinctive artistic styles of individual illustrators. These contextual elements shape the visual expression of the covers while preserving the core semiotic identity of the novel.